Analysis of the Role of Social Media in the Collective Trauma of Middle Eastern Societies : A Digital Analysis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (Calory Journal Medical Laboratory Journal, 2025)
This study comprehensively examines the impact of social media on the formation and intensification of collective trauma in the Middle East through a digital meta-analytical approach synthesizing 47 empirical studies, encompassing a total of 31,842 participants, published between 2015 and 2024. The results reveal a strong and statistically significant correlation between the intensity of social media use and levels of collective trauma, with a correlation coefficient of r = 0.67 and a p-value of < 0.001, indicating a consistent and substantive relationship. Furthermore, regression analysis indicates that exposure to violent content through social media accounts for 43.2 percent of the variance in communal post-traumatic stress symptoms, affirming the role of digital media as a significant catalyst in amplifying collective psychological responses to conflict in the Middle East. Daily social media use exceeding five hours was found to significantly increase the risk of experiencing collective trauma by 2.8 times, with an odds ratio of 2.84 and a 95 percent confidence interval ranging from 2.31 to 3.49. Platforms such as Facebook and Twitter demonstrated a more substantial influence in widely disseminating traumatic experiences, with a beta coefficient of 0.58, compared to Instagram, which had a relatively lower influence with a beta value of 0.34, indicating that the structural and technological logic of each platform mediates the psychological transmission effect. Thematic analysis across studies revealed three primary mechanisms through which trauma is transmitted via social media: first, the amplification of traumatic narratives, accounting for 41.3 percent of identified patterns; second, the normalization of violence at 32.7 percent; and third, the reinforcement of collective identity based on shared traumatic experiences at 26.0 percent, thereby creating a digital ecosystem prone to the social accumulation of negative emotional states. These findings substantially expand the scope of prior research, such as that conducted by Atallah in 2017 and Nasciutti and Rahbari-Jawoko in 2021, which focused more narrowly on individual trauma, by highlighting a broader collective dimension and emphasizing the specific roles of various digital platforms in reinforcing these psychosocial dynamics. This study also identifies a novel pattern of both theoretical and practical significance, namely that algorithmic content recommendation contributes significantly to the formation of closed psychological echo chambers of trauma, intensifying exposure to traumatic content and deepening the affective impact of Middle Eastern conflict within digital spaces, with a significance level of p < 0.001. Accordingly, these findings underscore the urgent need for strategically designed and contextually grounded digital interventions to mitigate the burden of collective trauma in communities affected by protracted armed conflict in the Middle East.